Teori Darajat: Penyeimbang Double Burden - Ali Sobri; Dwi Noviani (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2023)
This study aims to analyze the double burden (double burden) of women. The development of the times has transformed the thoughts and movements of women so that they do not only function in the domestic sphere but also in the public sphere. Even though this is a form of gender inequality in one sex. This is very interesting to study using socialist feminist theory and the position of women in Islam in terms of gender analysis of the position of women in the household. The purpose of this research is to look further at the views of feminists and Islam in the double burden experienced by women in various regions. Data analysis techniques in this study used the analytical techniques proposed by Miles and Huberman, namely: data codification, data presentation and drawing conclusions. The result of this study is that the dual role of women in various areas carried out by previous research occurs because there is no knowledge and awareness that there is oppression that they experience, so that its continuity is considered normal. Islam views women and men as having an equal position even in matters of household which must be based on equal principles and an agreement between the two parties. The significance of this study is to offer a micro snapshot of the problem of multiple roles at certain loci and can provide a glimpse into the potential for similar research in other areas.